(untitled) (Materiali di Estetica. Terza serie, 2025)
The following paper recalls Renato Rozzi’s academic career, from his first experiences at the new Department of Sociology in Trento during the fervent and turbulent years of youthful protests, through his period at the University of Calabria with his campus model and its promise of an unprecedented international openness, to his appointment as associate professor at the University of Urbino, and, finally, his time in Verona, where he ends his career. This paper focuses on this final phase of his educational career path, in order to shed light on his pedagogical stance, and to his thought on the relationship between younger and older generations, a topic that deeply engaged him, until his very last days.